Divergent contribution of the MVA and MEP pathways to the formation of polyprenols and dolichols in Arabidopsis. Issue 8 (26th April 2023) - Lipko, Agata; Pączkowski, Cezary; Perez-Fons, Laura; Fraser, Paul D.; Kania, Magdalena; Hoffman-Sommer, Marta; Danikiewicz, Witold; Rohmer, Michel; Poznanski, Jaroslaw; Swiezewska, Ewa
Abstract : Isoprenoids, including dolichols (Dols) and polyprenols (Prens), are ubiquitous components of eukaryotic cells. In plant cells, there are two pathways that produce precursors utilized for isoprenoid biosynthesis: the mevalonate (MVA) pathway and the methylerythritol phosphate (MEP) pathway. In this work, the contribution of these two pathways to the biosynthesis of Prens and Dols was addressed using an in planta experimental model. Treatment of plants with pathway-specific inhibitors and analysis of the effects of various light conditions indicated distinct biosynthetic origin of Prens and Dols. Feeding with deuteriated, pathway-specific precursors revealed that Dols, present in leaves and roots, were derived from both MEP and MVA pathways and their relative contributions were modulated in response to precursor availability. In contrast, Prens, present in leaves, were almost exclusively synthesized via the MEP pathway. Furthermore, results obtained using a newly introduced here 'competitive' labeling method, designed so as to neutralize the imbalance of metabolic flow resulting from feeding with a single pathway-specific precursor, suggest that under these experimental conditions one fraction of Prens and Dols is synthesized solely from endogenous precursors (deoxyxylulose or mevalonate), while the other fraction is synthesized concomitantly from endogenous and exogenous precursors. Additionally, this report describes a novel methodology for quantitative separation of 2 H and 13 C distributions observed for isotopologues of metabolically labeled isoprenoids. Collectively, these in planta results show that Dol biosynthesis, which uses both pathways, is significantly modulated depending on pathway productivity, while Prens are consistently derived from the MEP pathway.